Trends in the Development of Innovative Science Teaching Materials for Earth Science Education: A Semantic Literature Review (2020–2025) - La Arfin La Arfin; Liftiah Liftiah; Bambang Subali; Arif Widiyatmoko (Journal of Educational Sciences, 2026)
The development of science and technology in the 21st century has brought about major changes in the world of education, especially in science learning. Science education has a strategic role in shaping a generation that is able to think critically, creatively, and environmentally. This study aims to explore and analyze trends in the development of innovative science teaching materials in the field of Earth Science Education during the period 2020–2025 using a semantic literature review approach. Semantic analysis was conducted on a number of journal articles indexed in Scopus, ERIC, and Google Scholar. The results of the study show a significant shift in the design and implementation of teaching materials towards technology-based and learner-centered learning approaches. The methods used in this review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) protocol, with the literature search process conducted through several academic databases such as Scopus and Google Scholar. Of the total 179 articles found, 39 studies met the inclusion criteria and were analyzed further. Innovations such as interactive e-modules, digital flipbooks, augmented reality (AR), virtual laboratories, and gamified learning environments have been dominant trends in the last five years.